Copper Promoted Regio‐ and Stereoselective Aminochlorination of Alkynes and Alkenes with NFSI. Issue 34 (16th May 2018) - Wang, Weilin; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: A simple and rapid copper‐promoted aminochlorination of unactivated alkynes and alkenes with N ‐fluorobenzenesulfonimide (NFSI) was developed. Two series of chloroenamines and chloroamines were obtained in good to high yields. The chlorinated enamines could be obtained in a single E  configuration. This reaction involved a radical process and the CuCl2 acted as the Cl source and NFSI as the N source. Abstract : Take it easy : A novel aminochlorination reaction of alkynes and alkenes was developed by using CuCl2 / N ‐fluorobenzenesulfonimide (NFSI). High yields and stereoselectivities of chloroenamines and chloroamines were obtained.